A cria????o do conhecimento na ind??stria de celulose: estudos de casos m??ltiplos - Pineyrua, Diego Gilberto Ferber (2015)
This thesis identifies the characteristics of the knowledge creation process in cellulose companies in the context of a complex adaptive system. The sector has a complex supply chain, including the steps of reforestation, timber, cellulose production and paper manufacturing. It is characterized by being capital intensive and labor-intensive, have forest based and strong land concentration, all of which lead to economic concentration. The cellulose industry has gone through major processes of mergers and acquisitions, where tacit knowledge is acquired and the new company needs to hire people with tacit knowledge, converting it into tacit knowledge of another person. It has an export bias and has significant technological advances. The application of the theory of complex adaptive systems in an organizational environment led to knowledge management in a new direction The process of knowledge creation, is a part of the activities of a knowledge management program. Studies on the tacit and explicit knowledge approach the investigation of the knowledge creation process. From the literature, it has been prepared eleven study proposals that formed the basis for the development of field research in five major companies in the cellulose sector, four in Brazil and one in Uruguay. With the development of propositions, assumptions have been made making the connection between the main research question, gathering the assumptions and propositions in two study centers, to thus form the basis of the integral guiding questionnaire interview script. The methodology of the study predicted the development of the method of multiple case studies, through which the information of the companies were analyzed together and crosswise. Empirical evidence shows that companies have few features of a knowledge organization. To the knowledge conversion modes proposed a new nomenclature for the process of knowledge creation, and adaptation, disclosure, disposition and internalization. It was observed by environmental monitoring forms the interaction and interdependence characteristics of a complex adaptive system in the companies surveyed. There is a relationship among suppliers, specialized companies, customers and competitors who maintain a flow of information and market trends. The information and external expertise enable the development of employees with skills to organize themselves quickly and redirect efforts to the entire organization. At the end we present the model of knowledge creation for the cellulose companies with shares used in the adaptation of the environment and organizational knowledge.